Strategi Pembentukan Kaderisasi Relawan Sadar Lingkungan Berbasis Technopreneurship - Ajeng Suci Ratnaningsih; Iis Suwartini; Isah Fitriani; Dwi Aristi; Feti Setyowati; Annisa Novasari (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This PKM aims to raise public awareness of environmental health and generate profits by utilizing household waste which has the potential as a source of technopreneurship-based creative economy which can be a strategy in suppressing waste production in Indonesia. Research Methodology: The method used in this PKM is in the form of outreach activities, counseling, training, and assistance in waste management and maggot caterpillar cultivation. Results: The result of this activity is the formation of environmentally conscious volunteers who can manage waste and cultivate maggot caterpillars in an organized, creative, and innovative manner using digital technology in their marketing Conclusions: The conclusion from the implementation of this activity is that there is a change in community behavior in managing household waste into something that is worth selling. The cadre of environmentally conscious volunteers is a community engaged in waste entrepreneurship as an effort to create an education center for waste management.